Interdecadal Distribution of Persistent Organic Pollutants in Deep-Sea Chemosynthetic Bivalves - Ikuta, Tetsuro; Nakajima, Ryota; Tsuchiya, Masashi; Chiba, Sanae; Fujikura, Katsunori (Frontiers in Marine Science, 2021)
Marine ecosystems are continuously subjected to anthropogenic environmental pollution. Understanding the spread of pollution and the potential risks it poses to deep-sea ecosystems is important for developing better conservation measures. Here, we identified non-negligible levels of persistent organic pollutants in deep-sea chemosynthetic bivalves with limited or no filter feeding. The bivalves were collected from two sites: one located near a highly populated region and the other located relatively far from human activity. Analyses of samples collected nearly every decade in a period of 30 years suggested that environmental policy restrictions might be effective in reducing chemical pollution. However, the detection of contamination in deep-sea chemosynthetic animals suggests that the pollution could be spreading globally to chemosynthetic organisms with limited or no feeding. To protect these highly endemic and vulnerable deep-sea chemosynthetic ecosystems, our findings indicate that further research on chemical contamination and its effects on these ecosystems is required.